2020
DOI: 10.1192/bjo.2020.108
|View full text |Cite
|
Sign up to set email alerts
|

Mental distress and its association with sociodemographic and economic characteristics: community-based household survey in Aceh, Indonesia

Abstract: Background The role of sociodemographic and economic characteristics in mental distress has been rarely investigated in Indonesia. Aims To investigate the prevalence of common mental disorders (CMD) and identify any associations between mental distress and sociodemographic and economic characteristics among communities living in urban and rural (peri-urban) areas. Method A community-based household survey was conducted in the province of Aceh, Indonesia, in 2018. The 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…Depression determination methods also influence the prevalence ratio; self-reported methods tend to have a higher prevalence (30%) than clinical diagnosis assessment (22%) [8]. The current study utilized self-reported methods using WHO-SRQ-20 [33][34][35]; however, it found a lower prevalence than the previous review [8]. A previous systematic review of 26 studies involving all measurement assessments conducted in 2011 concluded that the prevalence of major depressive disorder in type 2 DM was 14.5%, indicating a lower prevalence ratio [37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Depression determination methods also influence the prevalence ratio; self-reported methods tend to have a higher prevalence (30%) than clinical diagnosis assessment (22%) [8]. The current study utilized self-reported methods using WHO-SRQ-20 [33][34][35]; however, it found a lower prevalence than the previous review [8]. A previous systematic review of 26 studies involving all measurement assessments conducted in 2011 concluded that the prevalence of major depressive disorder in type 2 DM was 14.5%, indicating a lower prevalence ratio [37].…”
Section: Discussionmentioning
confidence: 99%
“…This study was approved by the Ethics Committee, the National Institute of Health Research and Development (NIHRD), the Ministry of Health, Republic, Indonesia. MHD status was determined by a WHO self-reporting questionnaire-20 (SRQ-20), [ 33 , 34 , 35 ] as acquired from RISKESDAS 2018 data ( Supplementary File S1 ). SRQ-20 is a tool used to measure common mental disorder symptoms [ 33 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Depresi adalah masalah global yang signifikan dalam kesehatan masyarakat dan salah satu penyebab utama disabilitas. Prevalensi depresi di Indonesia telah mencapai 3,7% dari total populasi atau sekitar 9 juta orang meskipun perkiraan Indonesian Family Life Survey (IFLS) pada tahun 2014 menunjukkan bahwa depresi dapat mencapai 21,8% pada orang dewasa (Reuter et al, 2020). besitas dan depresi adalah penyakit yang umum diderita dan mempengaruhi banyak golongan umur dan komunitas diseluruh dunia (Wyatt et al, 2015).…”
Section: Hasil Dan Pembahasanunclassified